2008
DOI: 10.1038/ejhg.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of PTPN22: association of the 1858T-allele with Addison's disease

Abstract: The tyrosine-protein phosphatase non-receptor type 22 (PTPN22) gene was recently identified as an important genetic susceptibility factor in several autoimmune diseases. The increased risk has been broadly explained by the 1858T-allele (rs2476601). As two smaller studies on Addison's disease (AD) have shown diverging results, we aimed to elucidate the predisposing effect of the single-nucleotide polymorphism (SNP) 1858CT in a larger population of AD patients, especially focusing on the AD patients with known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 37 publications
1
43
0
3
Order By: Relevance
“…The highest T allele frequency (17.5%) was reported in northeast Russia, 14 followed by Finland (15.4%), 15 Ukraine (14.1%) 16 and Estonia (13.9%). 17 The frequency decreased toward the west, showing 11-13% in Poland, [18][19][20] 10-12% in Sweden, [21][22][23] Norway [24][25][26] and Germany, 24,[27][28][29] 11.7% in Croatia, 10-11% in the Czech Republic, 30,31 10.7% in Slovakia, 32 9.2% in Denmark, 33 and 8-10% in the UK [34][35][36][37][38][39] and the Netherlands. 24,[40][41][42] The decrease in the frequency toward the south was dramatic, with 7.75% in Hungary, 43 7.23% in Belgium, 7-8% in France, 44,45 5-7% in Spain 46-48 and 4.1% in Romania.…”
Section: Frequency Of the Ptpn22 Minor Allelementioning
confidence: 99%
See 1 more Smart Citation
“…The highest T allele frequency (17.5%) was reported in northeast Russia, 14 followed by Finland (15.4%), 15 Ukraine (14.1%) 16 and Estonia (13.9%). 17 The frequency decreased toward the west, showing 11-13% in Poland, [18][19][20] 10-12% in Sweden, [21][22][23] Norway [24][25][26] and Germany, 24,[27][28][29] 11.7% in Croatia, 10-11% in the Czech Republic, 30,31 10.7% in Slovakia, 32 9.2% in Denmark, 33 and 8-10% in the UK [34][35][36][37][38][39] and the Netherlands. 24,[40][41][42] The decrease in the frequency toward the south was dramatic, with 7.75% in Hungary, 43 7.23% in Belgium, 7-8% in France, 44,45 5-7% in Spain 46-48 and 4.1% in Romania.…”
Section: Frequency Of the Ptpn22 Minor Allelementioning
confidence: 99%
“…Three showed a significant association, whereas the other three studies showed a tendency toward a positive association but failed to reach the significance threshold. 25,87,109,110 Meta-analysis showed a significant association between the T allele and Addison's disease (OR ¼ 1.43; 95% CI ¼ 1.21-1.68, P ¼ 2.36 Â 10 À 5 ) (Figure 2e). Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis includes Wegener's granulomatosis, microscopic polyangiitis and Churg-Strauss syndrome.…”
mentioning
confidence: 99%
“…The CTLA-4 gene polymorphism and the PTPN22 gene polymorphism have been found to modulate genetic risk for AAD (Falorni et al, 2008;Skinningsrud et al, 2008a). A recent metanalysis of European studies has confirmed that the CTLA-4 Ala 17 polymorphism is strongly associated with genetic risk for AAD, independentenly from the well known association with the polymorphism of HLA class II genes (Brozzetti et al, 2010b).…”
Section: Genetics Of Autoimmune Adrenal Insufficiencymentioning
confidence: 89%
“…1, G788A, rs33996649, MAF≈2% (minor allele frequencies) внутри каталитиче-ского домена PTPN22 приводит к уменьшению фосфа-тазной активности и ассоциирована с уменьшенным риском возникновения системной красной волчанки (СКВ) [15]. Протективные свойства аллеля Q 263 рас-пространяются и на болезнь Адиссона [16], но не диа-бет первого типа [17]. Первые сообщения об ассоциации с СД1 полиморфизма R620W (C1858T, rs2476601) были опубликованы в 2004 г.…”
Section: /2013unclassified